Bovine papilloma virus (BPV)-encoded E1 protein contains multiple activities required for BPV DNA replication. - Seo, Y S (1993)
Replication of bovine papilloma virus (BPV) DNA requires two virus-encoded proteins, E1 and E2, while all other proteins are supplied by the host cell. Here, we describe the isolation of the E1 protein and show that it is a multifunctional protein. Purified E1 protein was required for the in vitro replication of BPV origin-containing DNA by extracts of mouse cells, as reported [Yang, L., Li, R., Mohr, I. J., Clark, R. & Botchan, M. R. (1991) Nature (London) 353, 628-632]. In addition, the E1 protein cosedimented with a number of other activities including (i) DNA helicase activity, (ii) BPV origin-containing DNA-specific binding activity, (iii) DNA-dependent ATPase activity, and (iv) BPV origin-specific unwinding of superhelical DNA. The E1 protein, acting as a helicase, moved in the 3'-->5' direction, like simian virus 40 (SV40) large tumor antigen, which plays a pivotal role in SV40 DNA replication. However, unlike the SV40 large tumor antigen, the helicase activity of E1 was stimulated 5-fold by the presence of a fork structure at the junction between single-stranded and double-stranded DNA and was supported efficiently by all eight nucleoside triphosphates. The E1-catalyzed ATPase activity required the presence of single-stranded or double-stranded DNAs.